Evaluasi Kelayakan Ekonomi Pertambangan Bauksit PT. Kapuas Bara Mineral di Kecamatan Tayan Hilir dan Balai, Kabupaten Sanggau, Provinsi Kalimantan Barat - , Muhammad Hery Setiyawan; R. Andy Erwin Wijaya (ReTII, 2022)
The potential of bauxite resources and reserves at the location of the mining business license of PT. Kapuas Bara Mineral currently needs to be optimized so that an evaluation of an economic and technical feasibility study. The area of ​​the mining business permit for the production operation of PT. Kapuas Bara Mineral covers an area of ​​9,245 hectares. The resource estimate is based on mineral conditions with an average overburden thickness of 2 meters, a total volume of 7,319,820 BCM and an average bauxite thickness of 6 meters obtained bauxite mined reserves of 20,344,000 WMT. The annual production capacity is targeted at 2,400,000 WMT of washed bauxite, then PT. Kapuas Bara Mineral can supply leached bauxite to the Smelter Grade Alumina Plant for 9 years. With Al2O3 content > 45% and bauxite concretion factor (CF) 56.78%. The initial investment that has been spent in financing the bauxite mining project is 7,450,462.85 USD. The method used in the analysis of the economic feasibility of a bauxite mining project at PT. Kapuas Bara Mineral with Net Present Value (NPV), Internal Rate of Return (IRR), and Pay Back Period (PBP) methods using 60% own capital and 40% loan capital with a minimum interest rate of 9.57% has an NPV of 44,812.118 USD, IRR of 116.52% and payback period of 2.04 years.